Chemical Enrichment at High Redshifts: Understanding the Nature of Damped Lyα Systems in Hierarchical Models - Tissera, Patricia Beatriz (2001)
We use cosmological hydrodynamical simulations including star formation and metal enrichment to study the evolution of the chemical properties of galaxy-like objects at high redshift in the range 0.25 < z < 2.35 in a hierarchical clustering scenario. We find that as the galactic objects are assembled, their gaseous components exhibit neutral hydrogen column densities with abundances and scatter comparable to those observed in damped Lyα systems (DLAs). The unweighted mean of abundance ratios and least-square linear regressions through the simulated DLAs yield intrinsic metallicity evolution for [Zn/H] and [Fe/H] consistent with results obtained from similar analyses of available observations. Our model statistically reproduces the mild evolution detected in the metallicity of the neutral hydrogen content of the universe, given by mass-weighted means, if observational constraints are considered (as suggested in 1998 by Boissée and co-workers). For the α-elements in the simulated DLAs, we find neither enhancement nor dependence on metallicity. Our results support the hypotheses that DLAs trace a variety of galactic objects with different formation histories and that both Type I and Type II supernovae are contributing to the chemical enrichment of the gas component, at least since z ≈ 2. This study indicates that DLAs could be understood as the building blocks that merged to form current normal galaxies within a hierarchical clustering scenario.